Римо-католицька громада Луцька в міжвоєнний період - Малеончук, Г. О.; Maleonchuk, Galina (Східноєвропейський національний університет імені Лесі Українки, 2017)
Охарактеризовано життя римо-католицької громади Луцька в 1920-1930-х рр. Виокремлено освітні, благодійні та просвітницькі організації лучан-католиків; проаналізовано методи їхньої роботи. Підкреслено роль єпископа Адольфа Шельонжека як ініціатора багатьох акцій католицької церкви в місті.The article deals with the life of the Roman Catholic community of Lutsk in 1920-1930-ies. A special attention has been devoted to the dynamics of changes of the population of Catholics in the city during the interwar period. Reference has also been made to the educational and charitable organizations of the Catholics. To these organizations belong the Lutsk Roman Catholic Community, the Catholic Church's Diocesan Institution; the Institution of Higher Religious Culture, Lutsk Diocesan Brotherhood of Christian Science. Their work was based on organization of lectures, courses, academies, charitable activities and distribution of printed products. «Lutsk Discipleship Month», «Catholic Life», «Bulletin of the Union of Polish Youth of the Lutsk Diocese» were periodical publications of the residents of Lutsk of the Catholic faith.
The Roman Catholic Community of Lutsk in the Interwar Period
Keywords: Луцьк; римо-католицька громада; Луцька дієцезія; єпископ Адольф Шельонжек; католицька акція; Lutsk; Roman Catholic community; Lutsk diocese; bishop Adolf Shelonzhek; Catholic Action